PENGEMBANGAN IOT DENGAN ALAT PENGHEMAT LISTRIK UNTUK MENGONTROL PENGGUNAAN DAYA LISTRIK - St. Awaliah Maghfirah; Faisal Syafar; Darlan Sidik (UNM Journal of Technology and Vocational, 2023)
The government's policy "stay at home" is implemented to prevent and cope with Covid-19 in Indonesia, so it affects the increase of public electricity bills due to changes in lifestyles that spendmore time at home. The IoT with an electricity-saving device, it can controling electricity load useand will greatly help the community, especially in pandemic conditions as is the case now. Thedevelopment model used in this research is the waterfall development model. There are 5 stages thatare passed in this development, namely analysis, design, development, testing, and safety. The expertvalidation test was conducted by 2 lecturers to determine the reliability of the product that had beenmade and obtained a very reliable interpretation. Field trials in this study were conducted in severalcommunity homes that installed IoT with electricity-saving devices in Makassar city with 5respondents. This test was conducted to determine the quality of the product from the usability aspectand the average score of SUS (System Usability Scale) is 80. An IoT with an electricity-saving devicecan provide user convenience in controlling the use of lights and fans in one hand, and can save theelectrical power at home, in this case electronic items that have an inductive load because of thepresence of a capacitor as a capacitive load that prevents changes in the value of the electric voltage.